Model of Religious Character Development in Islamic Boarding School - Ratu Bai Rohimah; Lulu Tunjung Biru; Siti Muhibah; Istinganatul Ngulwiyah (L, 2022)
The purpose of this research understand and describe the character of religious moderation developed and implemented by Pondok Pesantren Ar Rahmah Pandeglang Banten. The rise of government programs related to moderation has touched various fields of education, one of which is pesantren as a prototype or model of anti-radical education integrated into learning materials. This research is descriptive qualitative with research targets are clerics and students. Data were collected by interview and observation techniques, analyzed by data analysis techniques, data reduction, displayed for later conclusions and verification so that valid findings were obtained. It can be concluded from this research that pesantren has no doubt its role as a basis for inculcating moderate understanding to fulfill the characteristics of Muslims that have been mentioned in the Qur'an, namely ummatan wasathan. Moderation material is delivered through intensive teaching based on the turats book with the kyai as a role model. The attitude of knowing the history of the struggle of the kiai and santri to seize and fight for Indonesian independence, is able to foster a sense of patriotism and love for the homeland and inflame the spirit of jihad among the santri.